Genetic evidence of a hybrid swarm between Alpine ibex (Capra ibex) and domestic goat (C. hircus) - Alice Brambilla; Noel Zehnder; Bruno Bassano; Luca Rossi; Christine Grossen (Evolutionary Applications, 2024)
Abstract Improving the understanding of the causes and effects of anthropogenic hybridization is fundamental to ensure species conservation, particularly in the case of hybridization between wild species and their domestic relatives. Knowledge is missing for many species also because of a lack of appropriate tools for hybrid identification. Here, coupling genotype and phenotype analysis, we carried out an extensive investigation of ongoing hybridization in Alpine ibex Capra ibex, a mountain ungulate of conservation concern from a genetic perspective. By genotyping 63 diagnostic and 465 neutral SNPs, 20 suspected hybrids and 126 Alpine ibex without suspicious phenotype, representing 8 populations across a major part of the species distribution, we found evidence for ongoing hybridization between Alpine ibex and domestic goat. We identified different levels of hybridization including backcrosses into both Alpine ibex and domestic goat. Our results suggest a lack of reproductive barriers between the two species and good survival and reproductive success of the hybrids. Hybridization was locally intense, like a hybrid swarm, but not spread across the rest of the species distribution. Most of the hybrids were discovered in two locations in the north‐west of Italy, while random sampling of individuals from different areas did not provide evidence of recent hybridization. Our method, based on amplicon sequencing of 63 diagnostic SNPs specifically developed for this purpose, allowed us to identify hybrids and backcrosses up to the fourth to fifth generations and was suitable for genetic samples of different quality, although with varying levels of certainty regarding the exact number of generations passed since hybridization. Based on the paired analysis of genotype and phenotype, we provide guidelines for the first identification of hybrids in the field and suggest a procedure for the reliable identification of hybrids.